Three-Stage Dynamic Games of Government-Park-Visitor in Visitor Education Intervention - Dongping Wei; Shouwen Wen; Diabate Ardjouman; Yizeng Chen (Journal of Applied Mathematics)
The government-park-visitor three-stage multiplayers dynamic game G(S1m,S2n,S3k,RG,R,U) is established to solve the significant problem regarding the investment in the visitor education. The game reveals that the visitor education intervention should form a positive interaction mechanism of government leading, tourism enterprise implementing, and tourist participating. The visitor education system in the tourism market has not been established at the initial stage. Stakeholders are hesitant to invest resources to push the establishment of visitor education system. The government should set up an induction fund which can encourage the parks and tourism companies to invest money on visitor education. When visitor education system develops to a certain stage with the help of government induction fund, it can run autonomously without the external factors. And the win-win-win situation of the government, parks, and visitors is obtained when the Nash equilibrium state of the game is reached. Furthermore, the game also reveals that visitor education mainly includes the behavior intervention and knowledge services which are important for the park’s visitor education.